Penerapan Metode Pembelajaran Mind Mapping Sebagai Upaya Peningkatan Hasil Belajar Siswa Pada Pelajaran Bahasa Indonesia Kelas VII MTs Raudhatul Ulum Aek Nabara - Rezky Ramadani Rambe; Rahmad Idris Hasibuan (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
This research aims to describe the learning process and outcomes through the use of the Mind Map method. This research uses the Action research research method, starting from: a) planning, b) action and observation, c) reflection. The research process was carried out in two cycles. The research subjects were 28 class VII students at MTs Raudhatul Ulum, consisting of 13 men and 15 women. Data was collected through tests, observations, interviews and documentation studies. Data analysis techniques use qualitative and quantitative data analysis. The results showed improvement after learning using the mind mapping method. Pre-action was carried out to determine the percentage of learning outcomes of 46.77%, increasing to 70.39% after the first cycle, and increasing to 82.22% after the second cycle.